Dampak Keterlibatan Institusi Keuangan terhadap Sophistication Finansial dan Pengeluaran Konsumen - Benardi Benardi; Ngadi Permana; Mohammad Chaidir (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to examine the impact of financial institutions' involvement on financial sophistication and consumer spending through a literature review. Various relevant studies indicate that financial institutions' involvement through financial education, innovative financial products, and financial literacy can enhance consumers' understanding in making smarter financial decisions. These positive impacts include better spending management and the shift from consumptive spending to long-term investments. However, the success of this involvement is influenced by social, economic, and psychological factors that affect the adoption and effectiveness of financial programs. This study concludes that financial institutions play a crucial role in increasing financial sophistication, but external factors need to be considered for optimal results.